The Harold of a New Age: Childe Harold I and II and Byron’s Rejection of Canonical Knowledge - Bernhard Jackson, Emily (Romanticism on the Net, 2006)
AbstractThe first two cantos of Childe Harold’s Pilgrimage remain the least frequently discussed of Byron’s major works. This article asserts that these unjustly neglected cantos are, in fact, central to any understanding of Byron’s larger oeuvre. They offer the first example of what will become a persistent leitmotif in all of his future works: an engagement with the question of how knowledge is produced, and how trustworthy knowledge claims truly are. Childe Harold I & II show Byron examining, and rejecting, conventional Georgian ideas about understanding and its formation -- particularly ideas about the connection between vision and knowledge. In their place, Byron suggests that the link between seeing and knowing is unreliable at best, and posits a version of knowledge itself as fluid, unstable, and undetermined in any objective sense. Harold’s first two cantos are thus a presage of Byronic things to come, for they are a first step down a path that will lead Byron to a complete repudiation of the notion of stable, reliable knowledge eight years later, in Don Juan.